Determination of Benzimidazoles Pesticides in Environmental Water Using Hollow Fiber Microextraction - Lee, Y.R.; Tian, M.; Row, K.H. (Asian Journal of Chemistry, 2012)
An extraction method for the analysis of benzimidazoles pesticides (carbendazim, tiabendazole and tiophanate-methyl) in environmental water was developed based on hollow fiber liquid-phase microextraction (HF-LPME) combined with HPLC. The influence of the different factors on the HF-LPME efficiency including the salt conentraction and extraction time were examined. The best HF-LPME conditions were as follows: 1-octanol impregnated in the pores of the hollow fiber, extraction time of 2 h and salt concentration of 0.25 g/mL. Under the optimized condition, provided very low concentrations 0.0001 μg/mL were detected, showing 0.2, 0.5 and 0.25 fold enrichment of carbendazim, thiabendazole and thiophanate-methy, respectively. This had higher selectivity and sensitivity than the other traditional methods.